Fair Tourism in South Korea: An Examination of Sustainable Supply Chain Management for Tourism - Seungah Chung; Jonathon Day (Tourism and Hospitality)
Fair Tourism (FT) is an emerging form of tourism in Korea. It serves as a response to the unethical and unsustainable practices of Korean tour operators by incorporating various sustainable tourism practices. Sustainable supply chain management is a vital element in the operationalization of FT, and yet, despite the increasing significance of FT, there is a dearth of research on the phenomenon. This research aims to bridge this gap by examining how practitioners define and implement FT. The current analysis is based on semi-structured interviews with 15 CEOs of FT companies. Through thematic analysis of the interviews, valuable insights into the establishment and execution of FT are uncovered. Tourism operations like FT promote positive outcomes in destination communities. The study defines FT as tourism where travelers contribute to the local economy while also promoting environmental and social sustainability. The study also examines the sustainable supply chain management operations of FT practitioners, using the Supply Chain Operations Reference (SCOR) model as a framework. It is evident that FT practitioners recognize the significance of sustainable supply chain management and strive to foster a culture of mutually respectful relationships, setting them apart from traditional sustainable tourism practices. Furthermore, this article highlights how FT practitioners incorporate sustainable tourism and sustainable supply chain management (SSCM) in their programs. They achieve this by collaborating with local partners, utilizing local resources, and actively engaging with their partners within the destinations in which they operate.